2004
DOI: 10.1136/bmj.38036.646030.ee
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the MTHFR C677T polymorphism on risk of neural tube defects: case-control study

Abstract: Homozygosity for the T allele of the C677T polymorphism of the gene encoding the folate dependent enzyme 5,10-methylenetetrahydrofolate reductase (MTHFR) is a risk factor for neural tube defects.1 Both the homozygous (TT) and heterozygous (CT) genotypes are associated with lower tissue concentrations of folate, higher homocysteine concentrations, and lower enzyme activity than the wild type (CC) genotype; these effects are more marked in homozygotes. Low folate and raised homocysteine levels in early pregnancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
94
0
2

Year Published

2005
2005
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 6 publications
3
94
0
2
Order By: Relevance
“…The ability to identify those who are more susceptible to having NTD-affected pregnancies -the object of some studies [43][44][45] -is an exciting challenge and may enable targeted programs to be developed, obviating the need for whole population strategies.…”
Section: Food Folate and Physical Activitymentioning
confidence: 99%
“…The ability to identify those who are more susceptible to having NTD-affected pregnancies -the object of some studies [43][44][45] -is an exciting challenge and may enable targeted programs to be developed, obviating the need for whole population strategies.…”
Section: Food Folate and Physical Activitymentioning
confidence: 99%
“…Recent studies have shown that approximately 50% of the Irish population have variations in the gene coding for an enzyme involved in folate metabolism, 5,10-methylenetetrahydrofolate reductase (7)(8)(9) . Such genetic variations may account for £26 % of NTDaffected births in Ireland (10) . The situation in other countries is different in that the overall incidence of NTD is lower and most of the affected pregnancies are terminated.…”
mentioning
confidence: 99%
“…Clearly, half the population are not born with an NTD. The real prevalence rate for NTD has dropped from a high of seven per 1000 births to about one per 1000 births (14) . Clearly, many of these children will be heterozygous for the variant and a substantial minority will be homozygous for the variant (15) .…”
Section: Neural-tube Defectsmentioning
confidence: 99%
“…The variant is very common in the Irish population and those of European origin, with a widely different prevalence worldwide. The prevalence of being homozygous or heterozygous for the variant is approximately 10% and 40% respectively (14) . Thus, over half the population have at least one flawed copy of this variant and thus in turn so does every child born in the country.…”
Section: Neural-tube Defectsmentioning
confidence: 99%
See 1 more Smart Citation